Family firms and the stock market performance of acquisitions and divestitures - Feldman, Emilie R.; Amit, Raphael; Villalonga, Belén (Strategic Management Journal, 2019)
Research Summary This paper explores the stock market performance of acquisitions and divestitures where both, one, or neither of the companies in the transaction are family firms. We find that acquirer shareholder returns are highest when family firms buy businesses from non‐family firm divesters, especially when family chief executive officer (CEO) acquirers buy businesses from non‐family CEO divesters. Additionally, divester shareholder returns are highest when family firms sell businesses to non‐family firm acquirers, especially when family CEO divesters sell businesses to non‐family CEO acquirers. These findings reveal that it is important to consider the characteristics of both the acquiring and divesting firms when analyzing acquisition and divestiture performance, and that the expected gains to family firm acquisitions and divestitures are driven by transactions in which the counterparties are non‐family firms. Managerial Summary This paper explores how investors react to acquisitions and divestitures where both, one, or neither of the companies in the deal are family firms. The stock market performance of acquiring firms is highest when family firms buy businesses from non‐family firms, relative to the other three possible combinations of family and non‐family firm acquirers and divesters. Likewise, the stock market performance of divesting firms is highest when family firms sell businesses to non‐family firms, again relative to the other three possible combinations of family and non‐family acquirers and divesters. These findings suggest that investors take into consideration the identities of both the acquiring and divesting firms when evaluating acquisitions and divestitures, and that this has significant implications for the expected performance gains of these transactions.